Fluorescent carbon dots with highly negative charges as a sensitive probe for real-time monitoring of bacterial viability. Issue 30 (18th July 2017) - Song, Yuxiang; Li, Hao; Lu, Fang; Wang, Huibo; Zhang, Mengling; Yang, Jinjing; Huang, Jian; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract : Doped carbon dots from a yeast extract were first applied in real-time monitoring of bacterial viability as a nano-thermometer. Abstract : Monitoring of bacterial viability is crucial for food safety and human health. Fluorescence staining with dyes is one of the simple and fast methods to assess bacterial viability. However, obtaining stable and non-poisonous dyes is still a huge challenge. Herein, we demonstrate that nitrogen, phosphorus and sulfur co-doped carbon dots (NPSCDs) can selectively stain dead bacteria rather than live ones because they possess a highly negative ζ potential (−41.9 mV), indicating that NPSCDs could serve as an efficient dye for bacterial viability evaluation. The NPSCDs were synthesized by one-step hydrothermal carbonization of a yeast extract, and exhibit favorable photoluminescence (PL) with high quantum yield (QY, 32%), excellent photostability (under acid/alkaline and strong ionic strength), good biocompatibility and low toxicity. Moreover, the designed NPSCDs show a precise response to temperature within the range from 30 °C to 90 °C, in which the fluorescence of the NPSCDs decreased linearly with an increase in temperature and recovered with a decrease in temperature. More importantly, when the live bacteria were incubated with NPSCDs, as the temperature increases, the NPSCDs could selectively stain dead bacteria in real time along with a decrease in fluorescence intensity simultaneously, showing a significant reduction in bacterial viability from 80% to 15% upon heating at 60 °C for more time. The development of NPSCDs paves a new way for the synthesis of a sensitive fluorescent probe that can be used in real-time monitoring of bacterial viability.